The impact on power semiconductor device operation due to local electric field alterations in the planar junction termination. (March 2016) - Rahimo, Munaf; Richter, Frank; Fischer, Fabian; Vemulapati, Umamaheswara; Kopta, Arnost; Corvasce, Chiara; Geissmann, Silvan; Bellini, Marco; Bayer, Martin; Bauer, Friedhelm
Abstract: In this paper, we present and discuss simulation and experimental results obtained from investigating the impact of local alterations of the electric field profile in the power device planar junction termination region. Such local modifications are due to possible various extrinsic causes (manufacturing, operational or environmental) and are shown to have a critical influence on the device voltage blocking capability and reliability. The results point towards junction termination sensitivity to locally modified fields especially under voltage switching conditions due to higher leakage current densities in the modified area compared to the rest of the JT region. Highlights: Local alterations of the device junction termination electric field are investigated. Local field alterations are critical for the device voltage blocking performance. Sensitivity to modified fields is pronounced under voltage switching conditions. Higher leakage currents in the modified area jeopardize device blocking stability. Design and protection of the JT are crucial for ensuring uniform electric fields.